2011
DOI: 10.1002/lary.22035
|View full text |Cite
|
Sign up to set email alerts
|

Cultured vestibular ganglion neurons demonstrate latent HSV1 reactivation

Abstract: Objectives/Hypothesis Vestibular neuritis is a common cause of both acute and chronic vestibular dysfunction. Multiple pathologies have been hypothesized to be the causative agent of vestibular neuritis; however, whether herpes simplex type I (HSV1) reactivation occurs within the vestibular ganglion has not been demonstrated previously by experimental evidence. We developed an in vitro system to study HSV1 infection of vestibular ganglion neurons (VGNs) using a cell culture model system. Study design basic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 40 publications
0
28
0
Order By: Relevance
“…The chemicals elevated in the stress response (cortisol and adrenalin) are capable of allowing the virus to reactivate [40] and cause symptoms by destroying groups (clusters) of ganglion cells. Reactivation of latent HSV-1 has been confirmed in animal-cultured (rat) vestibular ganglion cells [34]. A major deterrent to the acceptance of a viral neuropathy in these common vestibular syndromes is the lack of history pointing to a recognizable viral insult to the ear.…”
Section: Definitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The chemicals elevated in the stress response (cortisol and adrenalin) are capable of allowing the virus to reactivate [40] and cause symptoms by destroying groups (clusters) of ganglion cells. Reactivation of latent HSV-1 has been confirmed in animal-cultured (rat) vestibular ganglion cells [34]. A major deterrent to the acceptance of a viral neuropathy in these common vestibular syndromes is the lack of history pointing to a recognizable viral insult to the ear.…”
Section: Definitionsmentioning
confidence: 99%
“…This group of viruses has a propensity for invading sensory neurons, establishing latency within the nucleus of the ganglion cell, and becoming reactivated at a later (years) date during a period of extreme stress [32,33]. The best known members of this group of viruses are herpes simplex HSV types 1 and 2, and Herpes zoster (varicella) virus [34]. Other members of this family of NT viruses are cytomegalo-inclusion virus, pseudorabies and Epstein-Barr virus.…”
Section: Definitionsmentioning
confidence: 99%
“…There are two previously published models of in vitro HSV-1 lytic and latent infection in primary cultures of neuronal cells from the temporal bone. These are in vestibular ganglion neurons [34] and in geniculate ganglion neurons [35]. In this study, we have shown that infection of SGN culture with HSV-1 in the presence of ACV, which suppresses lytic replication, resulted in latent infection.…”
Section: Discussionmentioning
confidence: 79%
“…Patton has been used extensively in laboratory studies, including, but not limited to, early studies of mRNA splicing (Watson et al, 1981), identification of lytic cycle proteins involved in viral DNA replication (Graham et al, 1978), drug resistance (Furman et al, 1981), pathogenesis (Bonneau and Jennings, 1989; Mohr et al, 2001; Morahan et al, 1981; Ward et al, 2003), and oncolytic virus development (Pourchet et al, 2016; Taneja et al, 2001). The GFP-US11 recombinant has served as a versatile reporter simplifying the development of in vitro latency models (Camarena et al, 2010; Kuhn et al, 2012; Pourchet et al, 2017; Roehm et al, 2011), and has been used in more detailed studies of reactivation (Kim et al, 2012), maintenance of latency by nerve growth factor signaling (Camarena et al, 2010; Kobayashi et al, 2012), and the suppression of reactivation by interferon (Linderman et al, 2017). Understanding the genomic structure of Patton and its evolutionary relationship to other strains and clinical isolates is therefore important.…”
Section: Discussionmentioning
confidence: 99%